2007
DOI: 10.1111/j.1365-2052.2007.01606.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of population substructuring in Zimbabwe chicken ecotypes inferred using microsatellite analysis

Abstract: The objective of this study was to investigate the population structure of village chickens found in the five agro-ecological zones of Zimbabwe. Twenty-nine microsatellites were genotyped for chickens randomly selected from 13 populations, including the five eco-zones of Zimbabwe (n = 238), Malawi (n = 60), Sudan (n = 48) and six purebred lines (n = 180). A total of 280 alleles were observed in the 13 populations. Forty-eight of these alleles were unique to the Zimbabwe chicken ecotypes. The average number (+/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
124
15
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(168 citation statements)
references
References 26 publications
26
124
15
3
Order By: Relevance
“…The observed differences in the relationships between meat qualities traits among genotype could be related to the genetic variability of carcass traits that exist among those studied ecotypes (Tougan et al, 2013a). This result confirms the finding of Youssao et al (2010) who showed that indigenous chicken populations of Benin are characterized by a great genetic diversity than that reported for commercial lines chicken (Granevitze et al, 2007;Muchadeyi et al, 2007;Berthouly et al, 2008). In accordance with Havenstein et al (2003aHavenstein et al ( , 2003b, technological and nutritional meat quality depend on genotype.…”
Section: Discussion Correlations Between Technological and Nutritionasupporting
confidence: 80%
“…The observed differences in the relationships between meat qualities traits among genotype could be related to the genetic variability of carcass traits that exist among those studied ecotypes (Tougan et al, 2013a). This result confirms the finding of Youssao et al (2010) who showed that indigenous chicken populations of Benin are characterized by a great genetic diversity than that reported for commercial lines chicken (Granevitze et al, 2007;Muchadeyi et al, 2007;Berthouly et al, 2008). In accordance with Havenstein et al (2003aHavenstein et al ( , 2003b, technological and nutritional meat quality depend on genotype.…”
Section: Discussion Correlations Between Technological and Nutritionasupporting
confidence: 80%
“…Furthermore, the differentiation between Tanzanian chicken ecotypes (F ST 0.048) was found to be smaller than between commercial chicken lines. This is in agreement with several molecular studies, which revealed higher heterozygosity and lower F ST values between African local chickens than between commercial lines (Muchadeyi et al, 2007;Eltanany et al, 2011;Fosta et al, 2011;Goraga, et al, 2011;Mtileni et al, 2011a). In contrast to commercial lines, which have been managed as distant breeding populations for many generations, following a strict selection scheme, a higher genetic diversity in Tanzania chickens can be expected, as they are managed in a free-range system with random breeding and no selection for performance traits.…”
Section: Discussionsupporting
confidence: 76%
“…From molecular genetic marker analyses, the expected and observed heterozygosity estimates were higher in Tanzanian indigenous chickens compared with commercial breeds reported earlier (Granevitze et al, 2007;Muchadeyi et al, 2007;Bodzar et al, 2009;Fosta et al, 2011). Furthermore, the differentiation between Tanzanian chicken ecotypes (F ST 0.048) was found to be smaller than between commercial chicken lines.…”
Section: Discussionmentioning
confidence: 89%
“…For example, Hakka people prefer to keep their native chickens but they do not reproduce their own chicks, they always purchase large and sturdy chicks from hatchery or salesman irrespective to a specific breed (Lee, 2006). Such results are also consistent with values observed in village chickens in both Zimbabwe (Muchadeyi et al, 2007) and Ethiopia (Goraga et al, 2012) where local chickens have not been selected for performance traits and are managed in a free-range system. The F IS values ranged from 0.090 in Hakka strain to 0.283 in Golden chicken, which is a much larger range than the range observed in Taiwanese conserved chicken breeds (−0.053 to 0.068) by Berthouly et al (2008).…”
Section: Genetic Diversity Within Chicken Breedssupporting
confidence: 80%